(untitled) (Socio-economic relations in the digital society, 2019)
The thesis highlights the essence of the fundamental analysis and exchange rate and the scientifi c approach to forecasting exchange rate regimes studied by their classifi cation, analysis and synthesis of their essential properties, grounded theoretical and methodological approaches to the formation of the exchange rate in the context of the over all economic equilibrium Macroeconomic indicators are classifi ed, which are factors the volatility of the exchange rate by providing the following groups: economic growth, employment, consumer outlook, business outlook, housing, inflation, credit, financial and banking statistics and verbal intervention, foreign sector, budget, financial markets. There is reviewed the internal and external (specifi c) currency exchange rate factors. It is proved that there valuation of the base currency quotations (US dollar) causes a decline in world prices for export product sand growth of numerous macroeconomic imbalances in the national economic system.